Comparing pedagogical competence performances of English and non-English educational background teachers in teaching English at an elementary school - Dewi, Isna Rafika; Haryanti, Rahayu Puji; Faridi, Abdurrachman (Universitas Islam Sultan Agung, 2023)
Regulation of the Minister of National Education number 16 of 2007 stated that Teachers at the Elementary school level (SD/MI), or other equivalent forms, must have a minimum educational academic qualification of diploma four (D-IV) or bachelor (S1) in the field of Primary Education (D-IV/S1 PGSD/PGMI) or psychology obtained from an accredited study program. Thus, there are many schools that have English teachers from non-English educational backgrounds (NEB) rather than English teachers from English educational backgrounds (EEB). This condition will affect the quality of English teaching in Elementary schools. In order to evaluate further the suitability of government regulation regarding teachers’ criteria in teaching Elementary students, this study was to compare the pedagogical competence of English and non-English educational background teachers in teaching English at the elementary school level. The design of the study is qualitative research with a case study approach. The researcher took four English teachers consisting of two English teachers with EEB and two English teachers with NEB. This study used interviews, observation, and questionnaires to collect the data. This study used 10 indicators from the Ministry of Education, 2007. The results showed that from the 10 aspects, it can be highlighted that English teachers from EEB and English teachers from NEB have similarities and differences in implementing the indicators of pedagogical competence established by the Ministry of Education, 2007. It showed that the English teachers from EEB are more dominant in implementing indicators 1,2,8,9,10. Furthermore, the English teachers from NEB are more dominant in indicators 6 and 7. Thus, they have similarities in the rest of the indicators (3,4,5).